Clinimetric validity of the Trail Making Test Czech version in Parkinson's disease and normative data for older adults. (11th November 2017) - Bezdicek, Ondrej; Stepankova, Hana; Axelrod, Bradley N.; Nikolai, Tomas; Sulc, Zdenek; Jech, Robert; Růžička, Evžen; Kopecek, Miloslav
Abstract: Objective : The influence of demographic variables on the Trail Making Test (TMT) performance in older individuals and empirical findings on clinical validity in predementia states, such as Parkinson's disease mild cognitive impairment (PD-MCI), are limited. The principal aim of this study was to add normative data for the Czech population of older adults and explore the clinimetric properties between PD-MCI and PD patients with normal cognition (PD-NC).Method: The study included 125 PD patients classified as 77 PD-MCI and 48 PD-NC and 528 older individuals (60–74 years, further subdivided for normative tables into 60–64, 65–69 and 70–74 age groups) and very old individuals (aged 75–96, further subdivided into 75–79, 80–84, 85–96) cognitively intact Czech adults.Results: Mostly age, to a lesser extent education but not gender, was associated with most TMT basic and derived indices (TMT-B – A). However, the ratio of TMT-B/TMT-A was independent of both age and education. We provide corresponding T -scores that minimize the effect of demographic variables. The results showed a high discriminative validity of TMT basic and derived indices for the differentiation of PD-MCI from PD-NC (all p < .05). The classification accuracy for the differentiation of PD-MCI from controls was optimal for the TMT-B only (80% area under the curve) based on norm adjusted scores. The classification accuracy of the TMT for PD-MCI vs. PD-NC was suboptimal.Conclusions : The cut-offs and normative standards are useful in clinical practice for those working with PD patients and very old adults.